Perlindungan Hukum Terhadap Hak Ulayat: Pemberian Izin Usaha Pemanfaatan Hasil Hutan Kayu - Linda Martha Dona; Yurisa Martanti (Jurnal Nuansa Kenotariatan, 2016)
This research aim to examined how recognition of communal land set in the UUPA already recognized, but is still followed by certain conditions, it is often conflict between the holders of customary rights land by the government. This research is normative juridical empirical. Data collection techniques using literature study refers to the laws and regulations. Analysis data using juridical qualitative data analysis, data were obtained from the research literature and field research through library research and interviews, then analyzed with empirical juridical approach/sociological and methods of thinking inductive. The results showed that the customary rights sultan Taha Syariffuddin not recognized in the laws and regulations and local authorities for not fulfill the requirements, so efforts to completion of conflict heirs of the Sultan Taha Syariffudin with PT LAJ not have bargaining power over that required recognition and legal protection of the traditional rights on lands of indigenous communities have not been granted by the local government as well as the laws.